Veterinary and sanitary assessment of fish and seafood by quality and safety indicators - Kotelevych, V.; Huralska, S.; Hоncharenko V. (Scientific Progress & Innovations, 2023)
Fish and seafood are unique products in terms of nutrients, biological value, profitability of production and demand in the consumer market, important components in the population's diet. However, 85 % of the Ukrainian fish market is imported, which is not always of the proper quality. Our state imports fish and seafood from 60 countries of the world, and its imports are growing every year. In recent years, the culinary traditions of Korea, Japan, China and other Southeast Asian countries, in which many dishes are prepared from raw or semi-raw fish, crustaceans, squid and other molluscs, have become widespread in Ukraine. This poses a great danger of human infection with zoonoses, in particular, invasive ones. Fish is one of the most nutritious and perishable foods. Outbreaks of food-borne zoonoses in humans can occur both as a result of the use of fish products obtained from sick fish, and as a result of secondary contamination in the process of procurement, disassembly, storage in refrigerators and food production. Freshwater fish can be carriers of Escherichia coli, salmonella, protea and staphylococci due to sewage pollution. Fish and shellfish can be affected by pathogenic and potentially pathogenic bacteria: Streptococcus iniae, Clostridium botulinum type E, Vibrio vulnificus, Vibrio spp, Salmonella spp, Erysipelothrix rhusiopathiae, Listeria, aeromonads and others. The purpose of the review was to provide a veterinary and sanitary evaluation of fish and seafood according to quality and safety indicators in the light of modern research to ensure consumer safety. In the period of rapid development of the fishing industry and environmental pollution, the control of the content of potentially toxic elements in fish and seafood is of particular importance. One of the most dangerous are heavy metals. Almost all types of marine fish and shellfish have been found to contain traces of mercury. Some types of marine fish (sharks, swordfish, king mackerel, king mackerel) and shellfish contain high concentrations of mercury, which can harm the health of consumers. The increase in the volume of production and supply of fish and fish products to Ukraine determines the urgency of the issue of their veterinary and sanitary assessment based on quality and safety indicators. Considering the urgency of providing the residents of Ukraine with high-quality and safe fish products, it is extremely necessary to edit national standards regarding such indicators as the content of toxic elements, radionuclides, pesticides and other pollutants in accordance with the requirements of standards implemented in global practice, and to strengthen control over compliance with technical regulations when using fish and fish products.